THYROID CYST DISEASE, TREATMENT AND PREVENTION MEASURES - Kahhorova Feruza Mahmudovna (World Scientific Research Journal, 2025)
Abstract. The thyroid gland is an endocrine organ, that is, an organ that produces hormones. It is located almost directly under the skin at the front of the neck. Thyroid hormones (Thyroxine and triiodothyronine) regulate the metabolic process. In addition, the gland produces the hormone calcitosine, which is responsible for controlling calcium metabolism in the body.